2013
DOI: 10.1027/1618-3169/a000180
|View full text |Cite
|
Sign up to set email alerts
|

Object-Guided Spatial Selection in Touch Without Concurrent Changes in the Perceived Location of the Hands

Abstract: In an endogenous cueing paradigm with central visual cues, observers made speeded responses to tactile targets at the hands, which were either close together or far apart, and holding either two separate objects or one common object between them. When the hands were far apart, the response time costs associated with attending to the wrong hand were reduced when attention had to be shifted along one object jointly held by both hands compared to when it was shifted over the same distance but across separate obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Moreover, there is evidence for object-guided attention in touch. It has recently been demonstrated that attentional selection can be object driven, as its time course was shown to be modulated depending on whether the two hands were holding the same object or not 26 27 . This suggests that processing times will be reduced when information is contained within the same perceptual group, or object.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is evidence for object-guided attention in touch. It has recently been demonstrated that attentional selection can be object driven, as its time course was shown to be modulated depending on whether the two hands were holding the same object or not 26 27 . This suggests that processing times will be reduced when information is contained within the same perceptual group, or object.…”
Section: Discussionmentioning
confidence: 99%
“…Non-spatial attributes of attention have only very rarely been explored for the tactile domain. Recent ERP studies (Gillmeister et al, 2009(Gillmeister et al, , 2013 found evidence for object-based attention in touch. Selective attention to certain stimulus dimensions like orientation or frequency was also explored in several studies , which revealed decreased reaction times for valid compared to neutral cueing of the target's stimulus dimension , but did not find any cortical effects of attention .…”
Section: Somatosensory Attentionmentioning
confidence: 99%